Perancangan Rumah Warga Tua Berkonsep "Mesra Insan" Kajian Kes : Rumah Seri Kenangan Taiping, Perak Dan Bedong Kedah - Ab. Kadir, Abo. Avis Sukurny (2002)
Housing which provides protection and safety for man is one of the basic needs of human. Generally, in Malaysia up to the present, there are only a few old folks homes, which are set up as institutions that are run by the government and private sector. Many of these institutions were made into homes after covering the status of old buildings into welfare homes to place the aged and underprivileged those need protection, care and treatment. This case study was carried out on the Seri Kenangan Old Folks Home at Taiping, Perak and Bedong, Kedah. These two states were selected because of the high percentage of old people as compared to the other states in Malaysia.